Design and test of a novel crawler-type multi-channel air-assisted orchard sprayer - Qiu, Wei; Li, Xiaolong; Li, Chongchong; Ding, Weimin; Lv, Xiaolan; Liu, Yande (International Journal of Agricultural and Biological Engineering, 2020)
In order to solve the problem of poor traveling stability and excessive pesticide application during plant protection operations in hilly orchards, a novel crawler-type multi-channel air-assisted sprayer that is particularly appropriate for hilly orchards was designed in this study. Considering anti-rolling requirements and the orchard environment in hilly areas, this study selected limits for uphill and downhill rolling angles as well as the transverse rolling angle as the evaluation indexes for determining both the layout and parameter settings of the sprayer. According to freely submerged jets and the requirements in plant protection operation, a multi-channel air-assisted system was developed. The test results showed that the anti-rolling performance and the designed air-assisted system were adequate. At 2 m from the longitudinal center plane of the sprayer, the airflow exhibited wavy distribution patterns under different parameter combinations since the four streams of the airflow were not thoroughly intersected and mixed. At 3 m from the longitudinal center plane of the sprayer, the jet was ejected at great velocity but underwent rapid attenuation; the airflow velocity in most areas barely satisfied the requirements for plant protection operation. In addition, different air outlet layout schemes led to significant differences in the spatial distribution of the airflow field. Compared with a traditional air-assisted sprayer, using the developed multi-channel air-assisted sprayer enhanced the droplet coverage uniformity by 19.4%, and the mean droplet deposition in the front, middle, and rear of the canopy was enhanced by 32.9%, 50.3%, and 78.1%, respectively, while reducing ground deposition and air drift by 26.8%. Keywords: fan, dual-flow-channel, plant protection, air-assisted, test DOI: 10.25165/j.ijabe.20201306.5362 Citation: Qiu W, Li X L, Li C C, Ding W M, Lv X L, Liu Y D. Design and test of a novel crawler-type multi-channel air-assisted orchard sprayer. Int J Agric & Biol Eng, 2020; 13(6): 60–67.